Increasing access to infrastructure for Africa's rural poor - Torero, Máximo; Chowdhury, Shyamal (International Food Policy Research Institute, 2005)
The development community is increasingly in agreement that providing adequate hard infrastructure (i.e., capital-intensive infrastructure such as rural telecommunications, electrification, and rural roads) is an important step in the process of alleviating poverty and providing a more equitable set of opportunities for citizens in developing countries. In infrastructure development, Africa has lagged behind the Western Hemisphere for centuries, even trailing Latin America in recent decades.